Changes in the structure and mechanical properties of a typical coal induced by water immersion. (February 2021) - Ai, Ting; Wu, Shiyong; Zhang, Ru; Gao, Mingzhong; Zhou, Jifang; Xie, Jing; Ren, Li; Zhang, Zhaopeng
Abstract: Understanding fundamental aspects of the effects of water on both the mesostructure and mechanical characteristics of coal and coal-water interactions is important for increasing the utilization of coal and has not been thoroughly addressed by researchers. To fill this gap, a series of laboratory tests were carried out systematically using coal from the Tashan Coal Mine in China; both untreated samples and samples soaked for 3 h, 6 h, 12 h, 24 h, 36 h, 2 d, 4 d, 10 d, and 20 d. The water absorption characteristics, pore structure, mineral composition, surface morphology and wave velocities of the coal samples that varied with water-soaking time were studied comprehensively by using nuclear magnetic resonance, X-ray diffraction, scanning electron microscopy and ultrasonic testing. In addition, the mechanical properties, i.e., uniaxial compressive strength σ u and elastic modulus E, and the deformation and failure characteristics of the coal under different water-soaking periods were obtained by conducting uniaxial compression tests. The parameters of the water infusion techniques were also analyzed to address the hard coal roof of the Tashan coal mine. The results showed that as the water soaking time increased, the average pore sizes expanded and new pores developed; the pore types changed from micropores to mesopores to macropores. Longer water immersion led to not only greater pore connectivity and coal permeability but also changes in the mineral composition and structural characteristics. In addition, the velocity of the ultrasonic longitudinal wave first increased with seepage, enabling moisture to fill the macropores, and then decreased after 4 d due to the water wedge effect. Moreover, both σ u and E decreased and could be expressed by exponential functions in terms of soaking time; after 20 d, σ u and E decreased by 21.9% and 28.53%, respectively. The appropriate water infusion time and distance for advance were suggested to be 10–15 d and 60–90 m, respectively.